The effect of thickness on the physico-chemical properties of nanostructured ZnO:Al TCO thin films deposited on flexible PEN substrates by RF-magnetron sputtering from a nanopowder target. Issue 14 (1st November 2016) - Hamrit, S.; Djessas, K.; Brihi, N.; Viallet, B.; Medjnoun, K.; Grillo, S.E.
Abstract: Nanostructured aluminum-doped ZnO (ZnO:Al) thin films of various thicknesses were deposited on flexible Poly-Ethylene Naphthalate (PEN) substrates by RF-magnetron sputtering without intentionally heating them to fabricate Transparent Conductive Oxides (TCOs). The compacted ZnO:Al nanopowder with an [Al]/[Zn] ratio of 2%, which was synthesized by the sol-gel method combined with a supercritical drying process, was used as target in the sputtering system. The structural, morphological, optical and electrical properties of the deposited thin films of various thicknesses have been investigated. X-ray diffraction results indicate that all of the deposited thin films have a hexagonal wurtzite structure with c-axis orientation without any secondary phases. The Scanning Electron Microscopy (SEM) cross section images revealed that the films have a dense columnar nanostructure. The atomic percentage of the compositional elements in the films was nearly the same as that in the sputtering nanopowder target. Below a critical thickness of 500 nm, the films exhibit a high transmittance (>77% including the contribution of the PEN substrate) in the visible region. However, the electrical resistivity, Hall mobility and carrier concentration were significantly affected with the increase of film thickness. For thicknesses higher than 500 nm, the thin films exhibit similar electrical properties (resistivity of 3.5×10 −4 Ω cm and Hall mobility of 22 cm 2 V −1 s −1 ) but the transmittance decreases in the visible region. The Photoluminescence spectra showed that the Zn interstitial atoms, which enhance the conductivity of the films, are more dominant than the other defects.